Deep deuterium retention and Be/W mixing at tungsten coated surfaces in the JET divertor. (22nd January 2016) - Bergsåker, H; Bykov, I; Zhou, Y; Petersson, P; Possnert, G; Likonen, J; Pettersson, J; Koivuranta, S; Widdowson, A M
Abstract: Surface samples from a full poloidal set of divertor tiles exposed in JET through operations 2010–2012 with ITER-like wall have been investigated using SEM, SIMS, ICP-AES analysis and micro beam nuclear reaction analysis ( μ -NRA). Deposition of Be and retention of D is microscopically inhomogeneous. With careful overlaying of μ -NRA elemental maps with SEM images, it is possible to separate surface roughness effects from depth profiles at microscopically flat surface regions, without pits. With ( 3 He, p) μ -NRA at 3–5 MeV beam energy the accessible depth for D analysis in W is about 9 μ m, sufficient to access the W/Mo and Mo/W interfaces in the coatings and beyond, while for Be in W it is about 6 μ m. In these conditions, at all plasma wetted surfaces, D was found throughout the whole accessible depth at concentrations in the range 0.2–0.7 at% in W. Deuterium was found to be preferentially trapped at the W/Mo and Mo/W interfaces. Comparison is made with SIMS profiling, which also shows significant D trapping at the W/Mo interface. Mixing of Be and W occurs mainly in deposited layers.